Structural and functional studies of interactions between [beta]-1,3-glucan and the N-terminal domains of [beta]-1,3-glucan recognition proteins involved in insect innate immunity - Dai, Huaien (Kansas State University, 2013)
Insect [beta]-1,3-glucan recognition protein ([beta]GRP), a soluble receptor in the hemolymph, binds to the surfaces of bacteria and fungi and activates serine protease cascades that promote destruction of pathogens by means of melanization or expression of antimicrobial peptides. Delineation of mechanistic details of these processes may help develop strategies to control insect-borne diseases and economic losses. Multi-dimensional nuclear magnetic resonance (NMR) techniques were employed to solve the solution structure of the Indian meal moth (Plodia interpunctella) [beta]GRP N-terminal domain (N-[beta]GRP), which is sufficient to activate the prophenoloxidase (proPO) pathway resulting in melanin formation. This is the first determined three-dimensional structure of N-[beta]GRP, which adopts an immunoglobulin fold. Addition of laminarin, a [beta]-1,3 and [beta]-1,6 link-containing glucose polysaccharide (∼6 kDa) that activates the proPO pathway, to N-[beta]GRP results in the loss of NMR cross-peaks from the backbone [subscript]1[subscript]5N-[subscript]1H groups of the protein, suggesting the formation of a large complex. Analytical ultracentrifugation (AUC) studies of formation of the N-[beta]GRP:laminarin complex show that ligand binding induces self-association of the protein-carbohydrate complex into a macro structure, likely containing six protein and three laminarin molecules (∼102 kDa). The macro complex is quite stable, as it does not undergo dissociation upon dilution to submicromolar concentrations. The structural model thus derived from this study for the N-[beta]GRP:laminarin complex in solution differs from the one in which a single N-[beta]GRP molecule has been proposed to bind to a triple-helical form of laminarin on the basis of a X-ray crystal structure of the N-[beta]GRP:laminarihexaose complex. AUC studies and phenoloxidase activation measurements made with designed mutants of N-[beta]GRP indicate that electrostatic interactions between the ligand-bound protein molecules contribute to the stability of the N-[beta]GRP:laminarin complex and that a decreased stability results in a reduction of proPO activation. These novel findings suggest that ligand-induced self-association of the [beta]GRP:[beta]-1,3-glucan complex may form a platform on a microbial surface for recruitment of downstream proteases, as a means of amplification of the pathogen recognition signal. In the case of the homolog of GNBPA2 from Anopheles gambiae, the malaria-causing Plasmodium carrier, multiligand specificity was characterized, suggesting a functional diversity of the immunoglobulin domain structure.
Keywords: Innate immunity; 3-glucan; Carbohydrate-binding module; NMR; AUC[beta]-13-glucan; Biochemistry (0487); Biophysics (0786)